2019
DOI: 10.3174/ajnr.a6142
|View full text |Cite
|
Sign up to set email alerts
|

The Association between FLAIR Vascular Hyperintensity and Stroke Outcome Varies with Time from Onset

Abstract: BACKGROUND AND PURPOSE: FLAIR vascular hyperintensity has been recognized as a marker of collaterals in ischemic stroke, but the impact on outcome is still controversial. We hypothesized that the association between FLAIR vascular hyperintensity and outcome varies with time. MATERIALS AND METHODS: We included 459 consecutive patients with middle cerebral artery stroke and divided them into 3 groups by symptom-to-MR imaging time (group 1, Յ7 days; group 2, 8-14 days; group 3, Ն15 days). The FLAIR vascular hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Some studies demonstrated that the presence of FVHs was associated with severe clinical impairments and poor functional outcomes, ( Girot et al, 2007 ; Kufner et al, 2015 ; Dong et al, 2017 ; Nam et al, 2017 ; Zhu et al, 2020 ; Wang et al, 2021 ) whereas other studies indicated that FVHs were correlated with good collateral flow and favorable outcomes ( Pérez et al, 2012 ; Dong and Nao, 2019 ; Yuan et al, 2019 ; Aoki et al, 2020 ; Jiang et al, 2020b ; Wang et al, 2020 ; Zhou et al, 2020b ; Derraz et al, 2021 ). In addition, some other studies proposed that FVH has different clinical significance under different conditions regarding prognostic meaning other than information regarding arterial occlusion ( Kim et al, 2016 , 2019 ; Liu et al, 2016 ; Sakuta et al, 2016 ; Li et al, 2018 , 2021 ; Jiang et al, 2019 ; Shang et al, 2019 ; Zhou et al, 2020a ). Studies with prediction of FVH for functional outcomes are summarized in Tables 1 – 3 .…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies demonstrated that the presence of FVHs was associated with severe clinical impairments and poor functional outcomes, ( Girot et al, 2007 ; Kufner et al, 2015 ; Dong et al, 2017 ; Nam et al, 2017 ; Zhu et al, 2020 ; Wang et al, 2021 ) whereas other studies indicated that FVHs were correlated with good collateral flow and favorable outcomes ( Pérez et al, 2012 ; Dong and Nao, 2019 ; Yuan et al, 2019 ; Aoki et al, 2020 ; Jiang et al, 2020b ; Wang et al, 2020 ; Zhou et al, 2020b ; Derraz et al, 2021 ). In addition, some other studies proposed that FVH has different clinical significance under different conditions regarding prognostic meaning other than information regarding arterial occlusion ( Kim et al, 2016 , 2019 ; Liu et al, 2016 ; Sakuta et al, 2016 ; Li et al, 2018 , 2021 ; Jiang et al, 2019 ; Shang et al, 2019 ; Zhou et al, 2020a ). Studies with prediction of FVH for functional outcomes are summarized in Tables 1 – 3 .…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The association between FVH and functional outcomes varies with time. Shang et al (2019) reported that the symptom-to-imaging time might be an important factor when assessing the prognostic value of FVH. FVH is associated with unfavorable outcomes within 6 h to 14 days after onset, whereas a wider distribution of distal FVH may be favorable beyond 14 days after onset in infarction of the MCA.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Currently, research on the relationship between FVH and functional outcomes varies with time. The duration of time from symptom onset to imaging has been reported as an essential factor for evaluating the prognostic value of FVH [ 32 ]. In most studies that suggested a correlation between FVH and favorable outcomes, the time from symptom onset to imaging was less than 6 h [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, although FLAIR-HAs were not significant in the multivariate analysis, they were a significant predictor of poor functional outcomes in the univariate analysis. The FLAIR-HAs result from retrograde flow through the collateral arterial circulation and are related to the presence of large vessel stenosis or occlusion ( 22 ). The results of our study suggested that patients with large vessel occlusive disease should be considered as candidates for IV alteplase treatment even though presenting as minor stroke, and the LAD patient group should be defined into detailed subclassification according to various imaging parameters, such as the ratio of the penumbra to the infarct core in perfusion imaging studies, FLAIR-HAs in MR images, or diffusion–perfusion mismatch ratios.…”
Section: Discussionmentioning
confidence: 99%